Corporate Sustainability Performance: The Role of the Gender Diversity of the Board and Enterprise Risk Management - Mais, Rimi Gusliana; Hendra, Lim; Almurni, Siti; Maliki, Fanisyah (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
The research objective is to investigate the impact of board gender diversity on corporate sustainability performance, with enterprise risk management (ERM) as a moderating factor within health sector companies listed on the Indonesia Stock Exchange. The study adopts a secondary quantitative research approach and utilizes panel data linear regression analysis conducted through Econometric Views (E-Views). The study population consists of health sector firms listed on the Indonesia Stock Exchange from 2019 to 2022. The sample selection method used is purposive sampling, resulting in a sample size of 10 companies for the study. Secondary data is collected through the documentation method from the Indonesia Stock Exchange and the official websites of the selected companies. The findings reveal a negative relationship between board gender diversity and corporate sustainability performance, with a negative coefficient indicating that higher gender diversity among board members correlates with lower sustainability performance. Additionally, the study demonstrates that ERM strengthens the association between gender diversity and sustainability performance. Companies proficient in ERM implementation are better positioned to leverage the positive effects of gender diversity on sustainability performance. Understanding this interplay can assist organizations in making informed decisions regarding gender diversity policies and enterprise risk management strategies.